1976
DOI: 10.1002/hlca.19760590207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Vitamin A via Sulfones: A C15 Sulfone Route

Abstract: Reaction of vinyl-fl-ionol (1) [6] with the lithium or sodium salt of a sulfinic acid, essentially as described by Julia [5], gave the Cl5-sulfones 2 (a-k) 1) which on alkylation with l-acetoxy-3-chlormethyl-2-butene (3) [7] afforded the Czo-sulfones 4 (a-i) ; certain of these on base treatment furnished vitamin A (5). Table I lists the C15-and Czo-sulfones which were used in the present study.It was recognized at the onset that a major problem in this synthesis would be the elimination of the sulfinic acid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…It showed that 2,4-dinitrophenyl sulfone 1a was not suitable for the desired transformation, presumably due to an internal oxidation of the anion by the ortho nitro group that was also observed by Manchand et al 18 However, 4-nitrophenyl sulfones 1b-d were successfully applied in the modified Julia olefination (Scheme 1). Extensive investigations of different reaction conditions indicated that sodium hydride was the most efficient base for the reaction of unstabilized NP sulfone 1b and semistabilized NP sulfone 1c with aldehydes.…”
Section: Scheme 2 Synthesis Of Np Sulfones 1a-dmentioning
confidence: 77%
“…It showed that 2,4-dinitrophenyl sulfone 1a was not suitable for the desired transformation, presumably due to an internal oxidation of the anion by the ortho nitro group that was also observed by Manchand et al 18 However, 4-nitrophenyl sulfones 1b-d were successfully applied in the modified Julia olefination (Scheme 1). Extensive investigations of different reaction conditions indicated that sodium hydride was the most efficient base for the reaction of unstabilized NP sulfone 1b and semistabilized NP sulfone 1c with aldehydes.…”
Section: Scheme 2 Synthesis Of Np Sulfones 1a-dmentioning
confidence: 77%
“…The mixture was stirred for 30 min, and then bis(chloroallylic) sulfide 3 (2.53 g, 10.6 mmol) and NaI (3.81 g, 25.4 (d, J 10.6, 2 H); 6.06 (d, J 15.2, 2 H); 6.30 (dd, J 15.2, 10.6, 2 H); 7.43 ± 7.55 (m, 4 H); 7.55 ± 7.66 (m, 2 H); 7.73 ± 7.86 (m, 4 H). 15.9;16.9;17.7;25.7;26.5;28.1;37.5;40.1;63.8;110.0;121.8;123.8;124.7;124.8;126.2;128.8;129.1;131.7;133.2;133.5;137.7;140.9 [3,7,11,6,8,10,. Method A (Oxidation of 8).…”
Section: Experimental Partmentioning
confidence: 98%
“…608, respectively, according to the Karplus correlation [13]. Base-promoted anti-elimination of the H-atom and the PhSO 2 group then produced the (E)-CC bond at C(4) in conjugation with the other two CC bonds [7]. The (E)/(Z) stereoisomer ratios of the CC bond at C(2) in 7, however, deteriorated during this elimination process presumably due to an allylic migration of the anion at C(4), which might be formed under the harsh conditions in boiling EtOH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1. As the next synthetic strategy, a key intermediate which is assumed to produce an anion 7 ) useful for the generation of a C-C bond at the C-4 position of the pinene framework was considered. In our case, phenyl verbenyl sulfone 9 was adopted as the useful key intermediate.…”
mentioning
confidence: 99%